Emotion recognition and eye tracking of static and dynamic facial affect: A comparison of individuals with and without traumatic brain injury. Issue 7 (9th August 2022) - Greene, L; Barker, L. A; Reidy, J; Morton, N; Atherton, A
ABSTRACT: Diminished social functioning is often seen after traumatic brain injury (TBI). Mechanisms contributing to these deficits are poorly understood but thought to relate to impaired ability to recognize facial expressions. Static stimuli are often used to investigate ability post-TBI, and there is less evidence using more real-life dynamic stimuli. In addition, most studies rely on behavioral responses alone. The present study investigated the performance of a TBI group and matched non-TBI group on static and dynamic tasks using eye-tracking technology alongside behavioral measures. This is the first study to use eye tracking methodology alongside behavioral measures in emotion recognition tasks in people with brain injury. Eighteen individuals with heterogeneous TBI and 18 matched non-TBI participants were recruited. Stimuli representing six core emotions (Anger, Disgust, Fear, Happy, Sad, and Surprise faces) were selected from the Amsterdam Dynamic Facial Expression Set (ADFES). Participants were instructed to identify the emotion displayed correctly whilst eye movement metrics were recorded. Results: Results of analyses showed that TBI patients had First Fixation to nose for all emotion stimuli, shorter Fixation Duration and lower Fixation Count to eyes, were generally slower to classify stimuli, and less accurate than non-TBI group for the static task. Those with TBI were also less accurate at identifying Angry, Disgust, and Fear stimulus faces compared to the non-TBI group during the dynamic unfolding of an emotion. Conclusion: In the present study, those with TBI had atypical eye scan patterns during emotion identification in the static emotion recognition task compared to the non-TBI group and were associated with lower identification accuracy on behavioral measures in both static and dynamic tasks. Findings suggest potential disruption to oculomotor systems vital for first stage perceptual processing. Arguably, these impairments may contribute to diminished social functioning.